Silicon-carbon negative pole piece, preparation method thereof and all-solid-state lithium ion battery
By forming a interface protective layer generated by the in situ reaction of inorganic silver salt and lithium belt on the negative active layer of the silicon carbon negative chip, the problem of low battery performance caused by the poor interface stability in the full solid lithium ion battery is solved. Tall electrical properties and longer service life.
Patent Information
- Application Number
- CN202411516030.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-28
AI Technical Summary
In all-solid-state lithium-ion batteries, the battery performance problem is poor due to poor interface stability between the silicon-carbon negative electrode sheet and the electrolyte.
On the negative active layer of the silicon carbon negative chin, the interface protective layer generated by the in situ reaction of in the original position of inorganic silver salt and lithium belt is formed. The materials include inorganic lithium salt and lithium-silver alloy. Uniformly scattered and tight contact to optimize the solid-solid interface.
It effectively improves the stability and electrical performance of the silicon-carbon negative electrode, reduces the interface resistance between the negative active layer and the solid electrolyte layer, and improves the first-cycle Coulombic efficiency and cycle life of lithium-ion batteries.
Smart Images

Figure BDA0005106763710000101 
Figure BDA0005106763710000111
Abstract
Description
Technical Field
[0001] The present invention relates to the field of lithium-ion batteries, and in particular to a silicon-carbon negative electrode sheet, a preparation method thereof, and an all-solid-state lithium-ion battery. Background Art
[0002] At present, all-solid-state batteries with both high safety and high energy density have become the hottest battery system in the field of new energy. Among them, sulfide electrolytes have the most hope for successful commercial application in all-solid-state battery products due to their intrinsic characteristics of high ionic conductivity and good flexibility. Silicon-carbon negative electrodes, due to their advantages of high specific capacity and low redox potential, are the most promising negative electrode materials to match high-nickel ternary positive electrodes to realize commercial sulfide all-solid-state battery products.
[0003] However, the low conductivity, low first-cycle coulombic efficiency and poor solid-solid interface stability of the silicon-carbon anode and sulfide electrolyte have seriously affected the rate characteristics, energy density and cycle life of all-solid batteries. Therefore, how to regulate the solid-solid interface compatibility between the silicon-carbon anode and sulfide electrolyte, reduce the side reactions on the interface and improve the charge / ion transfer behavior on the interface are important scientific issues that need to be solved in the commercialization of all-solid-state lithium-ion batteries.
[0004] Based on this, how to provide a lithium-ion battery negative electrode plate with excellent performance to improve the interface stability between the negative electrode plate and the sulfide electrolyte, and then improve the electrical performance of the all-solid-state lithium-ion battery in which it is located, is one of the important technical problems that need to be solved in this field. Summary of the invention
[0005] The main purpose of the present invention is to provide a silicon-carbon negative electrode plate, a preparation method thereof and an all-solid-state lithium-ion battery, so as to solve the problem of poor battery performance in the all-solid-state lithium-ion battery in the prior art due to poor interface stability between the silicon-carbon negative electrode plate and the electrolyte.
[0006] In order to achieve the above-mentioned objectives, the first aspect of the present invention provides a silicon-carbon negative electrode plate, comprising: a negative electrode collector; a negative electrode active layer, arranged on at least one side surface of the negative electrode collector, the silicon-carbon negative electrode plate also comprises: an interface protection layer, arranged in contact with the surface of the negative electrode active layer away from the negative electrode collector, the material of the interface protection layer comprises a composite of an inorganic lithium salt and a lithium-silver alloy, and the interface protection layer is formed by an in-situ reaction of an inorganic silver salt and excess lithium strips on the surface of the negative electrode active layer.
[0007] The present invention effectively improves the stability and electrical performance of the silicon-carbon negative electrode plate where the interface protection layer is formed on the negative electrode active layer by an in-situ replacement reaction between an inorganic silver salt and a lithium belt. The inorganic lithium salt and the lithium-silver alloy in the interface protection layer are both generated by an in-situ replacement reaction between an inorganic silver salt and a lithium belt. Compared with directly physically mixing the inorganic lithium salt and the lithium-silver alloy as components to form a composite layer, the inorganic lithium salt and the lithium-silver alloy in the system generated by such an in-situ reaction can be dispersed more evenly and the physical contact between the two phases is closer, which ultimately optimizes the solid-solid interface more effectively and improves the performance of the plate and the battery. Compared with the silicon-carbon negative electrode interface protection layer commonly used in the art, which contains polymers such as polyvinylidene fluoride, polyethylene oxide, polyacrylonitrile, and polymethyl methacrylate, the negative electrode interface protection layer provided by the present invention, which contains lithium-silver alloy and inorganic lithium salt, has higher lithium ion conductivity, effectively reduces the interface resistance between the negative electrode active layer and the solid electrolyte layer, and also has higher electrolyte corrosion resistance and chemical stability, thereby being able to more significantly improve the electrical properties of the silicon-carbon negative electrode sheet in which it is located, and the performance of the corresponding lithium-ion battery.
[0008] In order to make the in-situ replacement reaction proceed more fully and obtain a silicon-carbon negative electrode sheet with higher structural consistency and better electrical performance, further, the inorganic silver salt is selected from one or more of silver oxide, silver carbonate, silver phosphate and silver chloride; and / or the inorganic lithium salt is selected from one or more of lithium oxide, lithium carbonate, lithium phosphate and lithium chloride.
[0009] Furthermore, the thickness of the interface protection layer is 10 μm to 15 μm, so as to suppress the obstruction of electron transmission caused by the excessive thickness of the protection layer, thereby more effectively improving the electrical performance of the negative electrode plate.
[0010] The second aspect of the present invention provides a method for preparing the above-mentioned silicon-carbon negative electrode sheet, which comprises: step S1, preparing a precursor dispersion containing an inorganic silver salt; step S2, coating the precursor dispersion onto the negative electrode active layer, and forming an inorganic silver salt layer on the negative electrode active layer; step S3, laminating an excess lithium tape on the surface of the inorganic silver salt layer in a direction away from the negative electrode active layer to obtain a composite layer including a lithium tape and an inorganic silver salt layer; step S4, heating the composite layer so that the inorganic silver salt and the lithium tape react in situ on the surface of the negative electrode active layer to obtain a sheet interface protection layer, and then obtaining a silicon-carbon negative electrode sheet.
[0011] With respect to the above-mentioned silicon-carbon negative electrode sheet, the present invention provides a preparation method thereof accordingly, wherein a precursor dispersion containing an inorganic silver salt is uniformly coated on the negative electrode active layer of the silicon-carbon negative electrode sheet, and then heated to allow the inorganic silver salt coated on the surface of the silicon-carbon negative electrode to react with lithium metal in situ, forming an interface protection layer whose main components are lithium-silver alloy and inorganic lithium salt.
[0012] Furthermore, the precursor dispersion was sprayed onto the negative electrode active layer in the form of droplets of 0.5 μm to 3.0 μm, with a spraying volume of 1.0 mL / cm 2 ~1.5mL / cm 2 Under this spraying condition, a more suitable in-situ reaction condition is constructed, and finally an interface protection layer that can provide effective protection is formed, which improves the electrical performance of the silicon-carbon negative electrode plate. Preferably, the thickness of the lithium strip is 5μm to 10μm, so as to promote the complete replacement reaction with the inorganic silver salt while more effectively suppressing the passivation reaction caused by excess lithium metal remaining on the surface, thereby more effectively improving the electrical performance of the electrode plate.
[0013] Furthermore, the precursor dispersion also includes a binder, and the weight ratio of the inorganic silver salt to the binder is (9-19):1, so as to better balance the adhesion, stability and conductivity, and more effectively improve the electrical properties of the silicon-carbon negative electrode sheet and the lithium-ion battery. Preferably, the binder is selected from one or more of polyvinylidene fluoride, polyacrylic acid and carboxymethyl cellulose, so as to further improve the electrical properties of the obtained electrode sheet by utilizing its better compatibility.
[0014] Further, in step S1, the preparation process of the precursor dispersion includes: dissolving the binder in an organic solvent to obtain an organic solution, and then adding the inorganic silver salt to the organic solution to obtain a precursor dispersion. Under this preparation condition, the system dispersion uniformity of the precursor dispersion is more effectively improved, and finally a silicon-carbon negative electrode sheet with a more continuous and stable structure and higher electrical performance is obtained. Preferably, based on the total weight of the organic solution as 100%, the amount of inorganic silver salt added is 20% to 25%, thereby obtaining an inorganic silver salt layer with a better structure, forming an interface protection layer that can play a more effective role, and the electrical performance of the obtained silicon-carbon negative electrode sheet is also higher. More preferably, the organic solvent is selected from one or more of N-methylpyrrolidone, acetonitrile and N,N-dimethylformamide, so as to improve the uniform dispersion of the inorganic silver salt and the binder, improve the uniformity and density of the obtained interface protection layer, and the electrical performance of the silicon-carbon negative electrode sheet.
[0015] Furthermore, both step S1 and step S2 are performed in a dry room environment; preferably, the temperature of the dry room environment is 20°C to 25°C, and the dew point is -60°C to -40°C. Such conditions can effectively reduce the water content of the inorganic silver salt layer, inhibit the introduction of impurities therein, enhance the intrinsic protective effect of the final interface protection layer, and optimize the binding property of the interface protection layer with the negative electrode active layer in the silicon-carbon negative electrode sheet, and finally obtain a silicon-carbon negative electrode sheet with better electrical performance.
[0016] Furthermore, the temperature of the heating treatment in step S4 is 50°C to 80°C, and the time is 0.5h to 2.0h; preferably, both step S3 and step S4 are performed in an environment with an oxygen content of less than 1ppm and a water content of less than 1ppm. Such conditions can reduce the occurrence of side reactions during the in-situ reaction to a greater extent, thereby further improving the purity and stability of the obtained interface protection layer, thereby making the corresponding silicon-carbon negative electrode sheet and lithium-ion battery have better performance, especially showing a higher first effect.
[0017] The third aspect of the present invention provides an all-solid-state lithium-ion battery, comprising a solid electrolyte layer, the all-solid-state lithium-ion battery is a full battery, the full battery comprises a positive electrode sheet, a negative electrode sheet and a solid electrolyte layer arranged between the positive electrode sheet and the negative electrode sheet; the positive electrode sheet comprises a positive electrode collector and a positive electrode active layer arranged on at least one side of the positive electrode collector, and the positive electrode active layer comprises a nickel-cobalt-manganese ternary layered oxide; the silicon-carbon negative electrode sheet is the above-mentioned silicon-carbon negative electrode sheet, or the silicon-carbon negative electrode sheet prepared by the preparation method of the above-mentioned silicon-carbon negative electrode sheet; or, the all-solid-state lithium-ion battery is a half-cell, the half-cell comprises a working electrode, a counter electrode and a solid electrolyte layer arranged between the working electrode and the counter electrode; the counter electrode is a lithium-indium electrode; the working electrode is the above-mentioned silicon-carbon negative electrode sheet, or the silicon-carbon negative electrode sheet prepared by the preparation method of the above-mentioned silicon-carbon negative electrode sheet; more preferably, the solid electrolyte in the solid electrolyte layer is selected from Li7P3S 11 , Li 10 GeP2S 12 , Li6PS5Cl, Li6PS5Br and Li6PS5I, more preferably Li6PS5Cl. The silicon-carbon negative electrode provided by the present invention contains an excellent interface protection layer, which can improve the compatibility, avoid direct contact between the negative electrode active material and the solid electrolyte during charging and discharging, thereby reducing the occurrence of side reactions, and also provide an additional lithium source for the lithium-ion battery in which it is located. Therefore, the all-solid-state lithium-ion full battery and half-battery containing the silicon-carbon negative electrode plate show excellent electrical properties, especially the first-cycle coulomb efficiency.
[0018] By applying the technical solution of the present invention, an interface protection layer generated by an in-situ replacement reaction between an inorganic silver salt and a lithium strip is formed on the negative electrode active layer, which effectively improves the compatibility of the negative electrode material and the electrolyte, reduces the direct contact between the negative electrode material and the electrolyte during the charge and discharge process, and thus reduces the occurrence of side reactions. At the same time, the lithium-silver alloy and the inorganic lithium salt in the interface protection layer can provide additional lithium sources, which helps to improve the first coulomb efficiency of the battery and extend the service life of the battery. DETAILED DESCRIPTION
[0019] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.
[0020] As described in the background art, the all-solid-state lithium-ion battery in the prior art has the problem of poor battery performance due to poor interface stability between the silicon-carbon negative electrode plate and the electrolyte. In order to solve the above technical problems, the first aspect of the present invention provides a silicon-carbon negative electrode plate, comprising: a negative electrode current collector; a negative electrode active layer, arranged on at least one side of the negative electrode current collector; the silicon-carbon negative electrode plate also includes: an interface protection layer, arranged in contact with the surface of the negative electrode active layer away from the negative electrode current collector, the material of the interface protection layer includes a composite of an inorganic lithium salt and a lithium-silver alloy, and the interface protection layer is formed by an inorganic silver salt and an excess lithium strip through an in-situ reaction on the surface of the negative electrode active layer.
[0021] The present invention effectively improves the stability and electrical performance of the silicon-carbon negative electrode plate by forming an interface protection layer generated by an in-situ replacement reaction between an inorganic silver salt and a lithium strip on the negative electrode active layer. Specifically, by setting an interface protection layer on the negative electrode active layer of the silicon-carbon negative electrode plate, that is, designing an interface protection layer between the negative electrode and the electrolyte, on the one hand, the excellent stability of the interface protection layer itself is utilized to avoid the interface side reaction caused by the direct contact between the two, and at the same time eliminate the high ion / electron transmission impedance caused by the interface gap. On the other hand, the lithium-silver alloy and the inorganic lithium salt component with high ionic conductivity contained in the interface protection layer promote the uniform and rapid transmission of lithium ions on the interface; wherein, the uniformly dispersed lithium-silver alloy can regulate the uniform distribution of lithium ion concentration on the interface, avoiding electrode rupture caused by local excessive reaction, and the inorganic lithium salt component with high ionic conductivity is beneficial to the rapid transmission of lithium ions, thereby avoiding the capacity attenuation and interface failure caused by lithium precipitation on the surface of the silicon-carbon negative electrode during high-rate charging. The above two reasons synergistically significantly improve the electrical performance of the resulting silicon-carbon negative electrode sheet, and ultimately make its corresponding all-solid-state lithium-ion battery exhibit high first-cycle coulombic efficiency.
[0022] Compared with the silicon-carbon negative electrode interface protection layer commonly used in the art, which contains polymers such as polyvinylidene fluoride, polyethylene oxide, polyacrylonitrile, and polymethyl methacrylate, the negative electrode interface protection layer provided by the present invention, which contains lithium-silver alloy and inorganic lithium salt, has higher lithium ion conductivity, effectively reduces the interface resistance between the negative electrode active layer and the solid electrolyte layer, and also has higher electrolyte corrosion resistance and chemical stability, thereby being able to more significantly improve the electrical properties of the silicon-carbon negative electrode sheet in which it is located, as well as the performance of the corresponding lithium-ion battery.
[0023] In particular, in the interface protection layer provided by the present invention and present on the silicon-carbon negative electrode plate, the inorganic lithium salt and the lithium-silver alloy are both generated by an in-situ substitution reaction between the inorganic silver salt and the lithium ribbon. Compared with directly physically mixing the inorganic lithium salt and the lithium-silver alloy as components to form a composite layer, the inorganic lithium salt and the lithium-silver alloy in the system generated by such an in-situ reaction can be dispersed more evenly and the physical contact between the two phases is closer, which ultimately more effectively optimizes the solid-solid interface and improves the performance of the plate and the battery.
[0024] In several preferred embodiments, the inorganic silver salt is selected from one or more of silver oxide, silver carbonate, silver phosphate and silver chloride; the inorganic lithium salt is selected from one or more of lithium oxide, lithium carbonate, lithium phosphate and lithium chloride. In order to make the in-situ replacement reaction more fully carried out and obtain a silicon-carbon negative electrode with higher structural consistency and better electrical performance, the inventors have selected the types of the above-mentioned inorganic silver salts and the corresponding types of inorganic lithium salts through a large number of experiments, and thus obtained a silicon-carbon negative electrode with better comprehensive performance, and the lithium-ion battery in which it is located also shows a higher first-cycle coulomb efficiency. The thickness of the preferred interface protection layer is 10μm to 15μm.
[0025] The second aspect of the present invention provides a method for preparing the above-mentioned silicon-carbon negative electrode sheet, which comprises: step S1, preparing a precursor dispersion containing an inorganic silver salt; step S2, coating the precursor dispersion onto the negative electrode active layer, and forming an inorganic silver salt layer on the negative electrode active layer; step S3, laminating an excess lithium tape on the surface of the inorganic silver salt layer in a direction away from the negative electrode active layer to obtain a composite layer including a lithium tape and an inorganic silver salt layer; step S4, heating the composite layer so that the inorganic silver salt and the lithium tape react in situ on the surface of the negative electrode active layer to obtain a sheet interface protection layer, and then obtaining a silicon-carbon negative electrode sheet.
[0026] With respect to the above-mentioned silicon-carbon negative electrode sheet, the present invention provides a preparation method thereof accordingly, wherein a precursor dispersion containing an inorganic silver salt is uniformly coated on the negative electrode active layer of the silicon-carbon negative electrode sheet, and then heated to allow the inorganic silver salt coated on the surface of the silicon-carbon negative electrode to react with lithium metal in situ, forming an interface protection layer whose main components are lithium-silver alloy and inorganic lithium salt.
[0027] Specifically, the heating process can accelerate the replacement reaction between the inorganic silver salt and the lithium ribbon, and improve the reaction rate and uniformity of the alloying reaction between the replaced silver metal and the lithium ribbon, thereby improving the process efficiency and the performance of the resulting silicon-carbon negative electrode sheet.
[0028] At the same time, in practical applications, the bonding between the lithium ribbon and the inorganic silver salt layer can be achieved by rolling, or by providing a certain pressure so that the two can be tightly combined to ensure the subsequent in-situ reaction.
[0029] Furthermore, after a large number of experiments, the inventors first transformed the precursor dispersion containing the inorganic silver salt into a droplet form by ultrasonic atomization, and the size of the precursor dispersion in the droplet form was preferably 0.5 μm to 3.0 μm, and the spraying amount was preferably 1.0 mL / cm 2 ~1.5mL / cm 2 , thus forming reaction sites with uniform dispersion and appropriate density, and simultaneously avoiding insufficient reaction due to excessive droplet size or spraying amount, and poor effect due to too small droplet size or spraying amount. Under this spraying condition, a more suitable in-situ reaction condition was constructed, and then by fitting a lithium strip larger than the silicon-carbon negative electrode and heating it, the generation of inorganic lithium salts and lithium-silver alloys was successfully achieved, and finally an interface protection layer that can provide effective protection was formed, which improved the electrical performance of the silicon-carbon negative electrode.
[0030] At the same time, the thickness of the lithium strip is preferably 5μm to 10μm, which can promote the complete replacement reaction with the inorganic silver salt and more effectively inhibit the excess lithium metal from remaining on the surface, causing a passivation reaction to generate a large number of by-products and destroying the interface structure. The surface of the pole piece after the replacement reaction and alloying reaction should have no obvious metallic luster.
[0031] In several typical embodiments, in order to obtain an interface protection layer with a more stable structure, it is preferred that the precursor dispersion also includes a binder. At the same time, the inventors have preferred the weight ratio of inorganic silver salt to binder to be (9-19):1 after a large number of experiments, so as to better balance the adhesion, stability and conductivity, and more effectively improve the electrical properties of the silicon-carbon negative electrode sheet and lithium-ion battery in which it is located. And, for the consideration of coordination and compatibility, the binder is preferably selected from one or more of polyvinylidene fluoride, polyacrylic acid and carboxymethyl cellulose, thereby obtaining a silicon-carbon negative electrode sheet with better electrical properties.
[0032] Furthermore, in order to improve the system dispersion uniformity of the precursor dispersion, and thus improve the structural density and integrity of the inorganic silver salt layer obtained during spraying and formation, and ultimately obtain a silicon-carbon negative electrode sheet with a more continuous and stable structure and higher electrical performance, in the preferred step S1, the preparation process of the precursor dispersion includes: dissolving the binder in an organic solvent to obtain an organic solution, and then adding the inorganic silver salt to the organic solution to obtain a precursor dispersion.
[0033] In order to better match the droplet size and spraying amount during the spraying process, the inventors have conducted a large number of experiments and preferably calculated the total weight of the organic solution as 100%, and the amount of inorganic silver salt added is 20% to 25%, thereby obtaining an inorganic silver salt layer with a better structure, thereby forming an interface protection layer that can play a more effective role, and the electrical properties of the resulting silicon-carbon negative electrode sheet are also higher. In several typical embodiments, the organic solvent is preferably selected from one or more of N-methylpyrrolidone, acetonitrile and N,N-dimethylformamide, so as to improve the uniform dispersion of the inorganic silver salt and the binder, improve the uniformity and density of the resulting interface protection layer, and the electrical properties of the silicon-carbon negative electrode sheet in which it is located.
[0034] In several typical implementations, in order to form an inorganic silver salt layer with a more stable structure, it is preferred that both step S1 and step S2 are performed in a dry room environment. The inventor further preferred that the temperature of the dry room environment be 20°C to 25°C and the dew point be -60°C to -40°C, so as to more effectively reduce the water content of the inorganic silver salt layer, inhibit the introduction of impurities therein, enhance the intrinsic protective effect of the final interface protection layer, and optimize the binding property of the interface protection layer with the negative electrode active layer in the silicon-carbon negative electrode sheet, and finally obtain a silicon-carbon negative electrode sheet with better electrical performance.
[0035] Regarding the in situ substitution reaction of inorganic silver salt and lithium ribbon, in order to effectively promote the in situ substitution reaction while inhibiting the material damage that may be caused during the reaction, the inventors have optimized the heating treatment temperature in step S4 to be 50°C to 80°C and the time to be 0.5h to 2.0h after a large number of experiments. Under these conditions, a negative electrode interface protection layer with a more stable structure and better performance was obtained, and the silicon-carbon negative electrode sheet and lithium-ion battery in which it is located also exhibited higher electrical performance accordingly.
[0036] In order to better promote the smooth progress of the in-situ exchange reaction, in several more typical embodiments, step S3 and step S4 are both carried out in a glove box with an oxygen content of less than 1ppm and a water content of less than 1ppm. At the same time, because the water and oxygen content in the glove box will change in real time, only a range value can be presented during the entire reaction process rather than a fixed value. The ultra-low oxygen and low water environment selected by the inventors after a large number of experiments can reduce the occurrence of side reactions during the in-situ reaction to a greater extent, thereby further improving the purity and stability of the obtained interface protection layer, and thus making the corresponding silicon-carbon negative electrode sheet and lithium-ion battery performance better, especially showing a higher first effect.
[0037] A third aspect of the present invention provides an all-solid-state lithium-ion battery comprising a solid electrolyte layer.
[0038] The all-solid-state lithium-ion battery is a full battery, which includes a positive electrode sheet, a negative electrode sheet, and a solid electrolyte layer disposed between the positive electrode sheet and the negative electrode sheet; the positive electrode sheet includes a positive current collector and a positive active layer disposed on at least one side of the positive current collector, and the positive active layer includes a nickel-cobalt-manganese ternary layered oxide; the negative electrode sheet is the above-mentioned silicon-carbon negative electrode sheet, or a silicon-carbon negative electrode sheet prepared by the above-mentioned method for preparing the silicon-carbon negative electrode sheet. Or, the all-solid-state lithium-ion battery is a half-cell, which includes a working electrode, a counter electrode, and a solid electrolyte layer disposed between the working electrode and the counter electrode; the counter electrode is a lithium-indium electrode; the working electrode is the above-mentioned silicon-carbon negative electrode sheet, or a silicon-carbon negative electrode sheet prepared by the above-mentioned method for preparing the silicon-carbon negative electrode sheet.
[0039] Because the silicon-carbon negative electrode plate provided by the present invention contains an interface protection layer with excellent performance, it can improve the compatibility and avoid direct contact between the negative electrode active material and the solid electrolyte during charging and discharging, thereby reducing the occurrence of side reactions. At the same time, it also provides an additional lithium source for the lithium-ion battery in which it is located. Therefore, the all-solid-state lithium-ion full battery and half-cell containing the silicon-carbon negative electrode plate both show excellent electrical properties, especially the first-cycle coulomb efficiency.
[0040] Specifically, the solid electrolyte layer has a thickness of 100 μm to 200 μm, and serves to provide an ion transmission channel and avoid short circuit between the positive and negative electrodes.
[0041] In several preferred embodiments, the solid electrolyte in the solid electrolyte layer includes but is not limited to Li7P3S 11 , Li 10 GeP2S 12 On this basis, Li6PS5Cl is more preferred because the inventors have found through a large number of experiments that the sulfide solid electrolyte can better cooperate with the above-mentioned interface protection layer, thereby obtaining an all-solid-state lithium-ion battery with higher first-efficiency.
[0042] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.
[0043] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0044] Example 1
[0045] A method for preparing a silicon-carbon negative electrode sheet:
[0046] In this embodiment, a silicon-carbon negative electrode sheet prepared by wet coating is used as the original silicon-carbon negative electrode sheet, wherein the mass ratio of silicon-carbon active material, sulfide electrolyte LPS5Cl, and polyacrylic acid binder is 16:4:1. The precursor materials selected for preparing the interface protection layer include inorganic silver salt as silver carbonate (Ag2CO3), binder as polyvinylidene fluoride (PvDF), organic solvent as N-methylpyrrolidone (NMP), and ultra-thin lithium strip with a thickness of 5μm. The specific implementation process is as follows:
[0047] S1. In a dry room environment with a temperature of 25°C and a dew point of -50°C, weigh 2 parts by mass of PvDF binder and add it to 98 parts by mass of NMP organic solvent, stir for 6 hours until the organic solution is clear and has no obvious particles, then add 25 parts by mass of Ag2CO3 inorganic silver salt and stir well to obtain a precursor dispersion (wherein the weight ratio of Ag2CO3 inorganic silver salt to PvDF binder is 12.5:1, and the amount of Ag2CO3 inorganic silver salt added relative to the organic solution is 25wt%);
[0048] S2: Also in a dry room environment with a temperature of 25°C and a dew point of -50°C, the precursor prepared in S1 was dispersed through an ultrasonic atomizer to form 0.5 μm droplets, which were then sprayed on the surface of the silicon-carbon negative electrode sheet. The amount of precursor solution sprayed per unit area of the silicon-carbon negative electrode sheet was 1.5 mL / cm 2 The sprayed electrode was transferred to a vacuum oven at 60°C for 12 hours, and after drying, a silicon-carbon electrode with a Ag2CO3 coating on the surface was obtained;
[0049] S3, in a glove box with an oxygen content of less than 1ppm and a water content of less than 1ppm, the electrode piece prepared in S2 is transferred to the glove box, and an ultra-thin lithium strip with a thickness of 5μm and a flexible non-woven fabric are sequentially attached to the surface of the silicon-carbon electrode piece, and the lithium strip and the Ag2CO3 coating on the silicon-carbon electrode piece are tightly attached by a roller press to obtain a composite electrode piece containing a composite layer;
[0050] S4. Similarly, in a glove box with an oxygen content of less than 1ppm and a water content of less than 1ppm, the composite electrode prepared in S3 was transferred to a heating table at 60°C for reaction for 0.5h, so that the elemental lithium in the lithium ribbon and the silver in Ag2CO3 underwent an in-situ substitution reaction. After the surface of the lithium ribbon lost its obvious metallic luster, the flexible non-woven fabric and the reacted lithium ribbon were removed to obtain a silicon-carbon electrode whose main components of the interface protection layer were lithium-silver alloy and lithium carbonate (Li2CO3), and the thickness of the interface protection layer was 10μm.
[0051] Example 2
[0052] A method for preparing a silicon-carbon negative electrode sheet:
[0053] In this embodiment, a silicon-carbon negative electrode sheet prepared by wet coating is used as the original silicon-carbon negative electrode sheet, wherein the mass ratio of silicon-carbon active material, sulfide electrolyte LPS5Cl, and polyacrylic acid binder is 16:4:1. The precursor materials selected for preparing the interface protection layer include inorganic silver salt as silver oxide (Ag2O), binder as polyvinylidene fluoride (PvDF), organic solvent as N-methylpyrrolidone (NMP), and ultra-thin lithium strip with a thickness of 5 μm. The specific implementation process is as follows:
[0054] S1. In a dry room environment at a temperature of 20°C and a dew point of -60°C, 2 parts by mass of PvDF binder were weighed and added to 98 parts by mass of NMP organic solvent, and stirred for 6 hours until the organic solution was clear and free of obvious particles, and then 20 parts by mass of Ag2O inorganic silver salt were added and stirred thoroughly to obtain a precursor dispersion (wherein the weight ratio of Ag2O inorganic silver salt to PvDF binder was 10:1, and the amount of Ag2O inorganic silver salt added relative to the organic solution was 20wt%);
[0055] S2: Also in a dry room environment with a temperature of 20°C and a dew point of -60°C, the precursor prepared in S1 was dispersed through an ultrasonic atomizer to form 3.0 μm droplets, which were then sprayed on the surface of the silicon-carbon negative electrode sheet. The amount of precursor solution sprayed per unit area of the silicon-carbon negative electrode sheet was 1.0 mL / cm 2 The sprayed electrode was transferred to a vacuum oven at 60°C for 12 hours, and after drying, a silicon-carbon electrode with a Ag2C coating on the surface was obtained;
[0056] S3, in a glove box with an oxygen content of <1ppm and a water content of <1ppm, the electrode piece prepared in S2 is transferred to the glove box, and an ultra-thin lithium strip with a thickness of 5μm and a flexible non-woven fabric are sequentially attached to the surface of the silicon-carbon electrode piece, and the lithium strip and the Ag2CO3 coating on the silicon-carbon electrode piece are tightly attached by a roller press to obtain a composite electrode piece containing a composite layer;
[0057] S4. Similarly, in a glove box with an oxygen content of less than 1ppm and a water content of less than 1ppm, the composite electrode prepared in S3 was transferred to a heating table at 60°C for reaction for 0.5h, so that the elemental lithium in the lithium strip and the silver in Ag2O underwent an in-situ substitution reaction. After the surface of the lithium strip lost its obvious metallic luster, the flexible non-woven fabric was removed to obtain a silicon-carbon electrode whose main components of the interface protection layer were lithium-silver alloy and lithium oxide (Li2O), and the thickness of the interface protection layer was 15μm.
[0058] Example 3
[0059] A method for preparing a silicon-carbon negative electrode sheet:
[0060] The difference between this embodiment and embodiment 1 is that the precursor materials selected for preparing the interface protection layer are different, specifically: the inorganic silver salt is silver phosphate (Ag3PO4), the binder is polyacrylic acid (PAA), the organic solvent is acetonitrile (ACN), and the ultra-thin lithium strip with a thickness of 10 μm. The amounts of each component and the parameter settings in the specific experimental conditions are the same.
[0061] Example 4
[0062] A method for preparing a silicon-carbon negative electrode sheet:
[0063] The difference between this embodiment and embodiment 1 is that the precursor materials selected for preparing the interface protection layer are different, specifically: the inorganic silver salt is silver chloride (AgCl), the binder is carboxymethyl cellulose (CMC), the organic solvent is N,N-dimethylformamide and the ultra-thin lithium strip with a thickness of 10 μm. The amounts of each component and the parameter settings in the specific experimental conditions are the same.
[0064] Example 5
[0065] A method for preparing a silicon-carbon negative electrode sheet:
[0066] The difference between this embodiment and embodiment 1 is only in step S1, specifically: weigh 2 parts by mass of PvDF binder and add it to 98 parts by mass of NMP organic solvent, stir for 6 hours until the organic solution is clear and has no obvious particulate matter, then add 16 parts by mass of Ag2CO3 inorganic silver salt and stir well to obtain a precursor dispersion (wherein the weight ratio of Ag2CO3 inorganic silver salt to PvDF binder is 8:1, and the amount of Ag2CO3 inorganic silver salt added to the organic solution is 16wt%).
[0067] Example 6
[0068] A method for preparing a silicon-carbon negative electrode sheet:
[0069] The difference between this embodiment and embodiment 1 is only in step S1, specifically: weigh 2 parts by mass of PvDF binder and add it to 98 parts by mass of NMP organic solvent, stir for 6 hours until the organic solution is clear and free of obvious particulate matter, then add 40 parts by mass of Ag2CO3 inorganic silver salt and stir well to obtain a precursor dispersion (wherein the weight ratio of Ag2CO3 inorganic silver salt to PvDF binder is 20:1, and the amount of Ag2CO3 inorganic silver salt added to the organic solution is 40wt%).
[0070] Example 7
[0071] A method for preparing a silicon-carbon negative electrode sheet:
[0072] The difference between this embodiment and embodiment 1 is that in step S2, the precursor dispersion is not subjected to ultrasonic atomization treatment, but is directly sprayed at 1.5 mL / cm 2 The coating amount is applied to the surface of the silicon-carbon negative electrode sheet, and then transferred to a vacuum oven at 60°C for 12 hours. After drying, a silicon-carbon electrode sheet with a surface coated with Ag2CO3 is obtained.
[0073] Comparative Example 1
[0074] The original silicon-carbon pole piece used in Example 1 without any treatment was directly used as the silicon-carbon negative electrode piece sample.
[0075] Comparative Example 2
[0076] A method for preparing a silicon-carbon negative electrode sheet:
[0077] The only difference between this embodiment and embodiment 1 is that in step S4, the composite pole piece is not heated, that is, the degree of in-situ reaction between the elemental lithium in the lithium strip and Ag2CO3 is low, and the interface protection layer of the obtained silicon-carbon pole piece correspondingly contains less inorganic lithium salt and lithium-silver alloy components and a large amount of precursor reactant components.
[0078] Comparative Example 3
[0079] A method for preparing a silicon-carbon negative electrode sheet:
[0080] In a dry room environment with a temperature of 25°C and a dew point of -50°C, metallic silver particles are spread on the surface of a lithium strip for alloying reaction, and a lithium-silver alloy strip is obtained after 2 hours of reaction.
[0081] In a dry room environment with a temperature of 25°C and a dew point of -50°C, 2 parts by mass of PvDF binder were weighed and added to 98 parts by mass of NMP organic solvent, and stirred for 6 hours until the organic solution was clear and free of obvious particulate matter, and then 12.5 parts by mass of Li2CO3 inorganic lithium salt were added and stirred thoroughly to obtain a mixed slurry; the mixed slurry was sprayed onto the silicon-carbon electrode in the manner of Example 1, and 12.5 parts by mass of lithium-silver alloy strips were spread on the surface of the sprayed electrode, and then transferred to a vacuum oven at 60°C for 12 hours, and the silicon-carbon negative electrode sample was directly obtained after drying.
[0082] That is, this comparative example uses Li2CO3 inorganic lithium salt and lithium silver alloy as components of the interface protection layer, and directly forms the interface protection layer on the surface of the original silicon-carbon negative electrode without undergoing an in-situ replacement reaction.
[0083] Test Method
[0084] 1. Preparation of half-cell samples:
[0085] Taking Example 1 as an example, the prepared silicon-carbon negative electrode sheet is used as the working electrode, Li6PS5Cl is used as the solid electrolyte, and a lithium-indium alloy sheet with a thickness of 100 μm is used as the counter electrode to prepare a half-cell sample. The specific steps are as follows:
[0086] (1) In a glove box, 0.1 g of Li6PS5Cl powder was slowly poured into and flattened in a Φ10 mm mold sleeve, a gasket and an upper pressure head were assembled, and the mold was placed in a tablet press workbench. A pressure of 2 t was applied at a uniform speed. After the pressure was maintained for 3 min, the tablet in the mold was ejected using a mold ejector sleeve to obtain a solid electrolyte membrane with a thickness of 200 μm.
[0087] (2) In a glove box, the silicon-carbon negative electrode sheet and the lithium-indium alloy prepared in Example 1 were cut into discs with a diameter of Φ10 mm, and the cut silicon-carbon negative electrode sheet, the solid electrolyte membrane, and the cut lithium-indium disc were slowly placed and flattened in the mold sleeve in sequence, and the gasket and the upper pressure head were assembled;
[0088] (3) Use a torque wrench to apply pressure to the assembled test device until the test pressure of the mold battery reaches 80 MPa, obtain the corresponding half-cell sample of Example 1, and perform subsequent electrochemical tests.
[0089] The preparation of the corresponding half-cell samples of the remaining embodiments and comparative examples was carried out in the above manner.
[0090] 2. Preparation of full battery samples:
[0091] Taking Example 1 as an example, the prepared silicon-carbon negative electrode sheet is used as the working electrode, Li6PS5Cl is used as the solid electrolyte, and the nickel-cobalt-manganese ternary layered oxide LiNi 0.8 Co 0.1 Mn 0.1 O2 is used as the positive electrode active material to prepare the full battery sample. The specific steps are as follows:
[0092] (1) A solid electrolyte membrane with a thickness of 200 μm was obtained according to the preparation method of the half-cell sample described above;
[0093] (2) Nickel-cobalt-manganese ternary layered oxide LiNi 0.8 Co 0.1 Mn 0.1 O2 was used as the active material for wet coating to obtain a positive electrode sheet, wherein the mass ratio of the active material, LPS5Cl sulfide electrolyte, carbon nanotube conductive agent and PvDF binder was 20:7:2:1;
[0094] (3) In a glove box, the silicon-carbon negative electrode sheet prepared in Example 1 and the positive electrode sheet prepared in (2) are cut into round pieces with a diameter of Φ10 mm, and the cut silicon-carbon negative electrode sheet, the solid electrolyte membrane, and the cut positive electrode sheet are slowly placed and flattened in the mold sleeve in sequence, and the gasket and the upper pressure head are assembled;
[0095] (4) Use a torque wrench to apply pressure to the assembled test device until the test pressure of the mold battery reaches 80 MPa, obtain the corresponding full battery sample of Example 1, and perform subsequent electrochemical tests.
[0096] The preparation of the corresponding full-battery samples of the remaining embodiments and comparative examples was carried out in the above manner.
[0097] 3. First-cycle coulombic efficiency of battery: For the silicon-carbon negative electrode sheets prepared in Examples 1-7 and Comparative Examples 1-3, half-cells and full cells were assembled according to the above method, and the first-cycle charge-discharge cycle was performed at a rate of 0.1C to obtain the first-cycle coulombic efficiency of the half-cell samples and full-cell samples corresponding to each embodiment and comparative example, as shown in Table 1 for details.
[0098] Table 1
[0099]
[0100]
[0101] From the above description, it can be seen that the above-mentioned embodiment of the present invention realizes the preparation of a silicon-carbon negative electrode plate including an interface protection layer, and the obtained silicon-carbon negative electrode plate has excellent performance and higher interface stability with the solid electrolyte layer, and the all-solid-state lithium-ion half-cell and the full cell in which it is located both show excellent first-cycle coulomb efficiency.
[0102] Specifically, Example 3 is a silicon-carbon negative electrode sheet whose interface components are inorganic lithium salt Li3PO4 and lithium-silver alloy, which exhibits the highest first-cycle coulomb efficiency of half-cell and full-cell, indicating that compared with inorganic lithium salts such as Li2CO3, Li2O and LiCl, Li3PO4 performs best in this interface system;
[0103] By comparing Examples 1, 5, and 6, it is not difficult to analyze that by adjusting the optimal ratio of inorganic lithium salt in the precursor solution (such as Example 1), a silicon-carbon negative electrode sheet with optimal interface protection layer performance can be obtained, and the assembled half-cell and full-cell both show higher first-cycle coulomb efficiency.
[0104] Combined with Comparative Examples 1-3, it is not difficult to analyze that the failure to take a heating step to promote the complete in-situ reaction of the lithium ribbon and the inorganic silver salt, and the direct coating of the inorganic lithium salt and the lithium-silver alloy without the in-situ reaction method to prepare the interface protection layer, can not obtain excellent first-cycle coulomb efficiency performance. The possible reasons are mainly incomplete reaction, small amount of expected products (inorganic lithium salt and lithium-silver alloy), large amount of residual precursors leading to complex interface components, affecting the interface ion transmission efficiency; and the direct coating method makes the two unable to disperse evenly, and the interface contact is poor, which seriously affects the interface ion transmission efficiency.
[0105] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the terms used in this way can be interchangeable where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those described herein, for example.
[0106] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A silicon-carbon negative electrode sheet, comprising: Anode current collector; A negative electrode active layer is disposed on at least one side of the negative electrode current collector; Characterized in that the silicon-carbon negative electrode plate also includes: An interface protection layer is arranged in contact with the surface of the negative electrode active layer away from the negative electrode current collector, and the material of the interface protection layer includes a composite of an inorganic lithium salt and a lithium-silver alloy, and the interface protection layer is formed by an inorganic silver salt and excess lithium strips through an in-situ reaction on the surface of the negative electrode active layer.
2. The silicon-carbon negative electrode sheet according to claim 1, characterized in that: The inorganic silver salt is selected from one or more of silver oxide, silver carbonate, silver phosphate and silver chloride; and / or the inorganic lithium salt is selected from one or more of lithium oxide, lithium carbonate, lithium phosphate and lithium chloride.
3. The silicon-carbon negative electrode sheet according to claim 1 or 2, characterized in that: The thickness of the interface protection layer is 10 μm to 15 μm.
4. A method for preparing a silicon-carbon negative electrode sheet according to any one of claims 1 to 3, characterized in that: The preparation method comprises: Step S1, preparing a precursor dispersion containing an inorganic silver salt; Step S2, coating the precursor dispersion onto the negative electrode active layer, and forming an inorganic silver salt layer on the negative electrode active layer; Step S3, laminating an excess lithium ribbon on the surface of the inorganic silver salt layer in a direction away from the negative electrode active layer to obtain a composite layer including the lithium ribbon and the inorganic silver salt layer; Step S4, heat-treating the composite layer so that the inorganic silver salt and the lithium ribbon react in situ on the surface of the negative electrode active layer to obtain the electrode interface protection layer, and then obtain the silicon-carbon negative electrode.
5. The preparation method according to claim 4, characterized in that: The precursor dispersion is sprayed onto the negative electrode active layer in the form of droplets of 0.5 μm to 3.0 μm, and the spraying amount is 1.0 mL / cm 2 ~1.5mL / cm 2 ; Preferably, the thickness of the lithium strip is 5 μm to 10 μm.
6. The preparation method according to claim 4 or 5, characterized in that: The precursor dispersion also includes a binder, and the weight ratio of the inorganic silver salt to the binder is (9-19):1; Preferably, the binder is selected from one or more of polyvinylidene fluoride, polyacrylic acid and carboxymethyl cellulose.
7. The preparation method according to claim 6, characterized in that: In step S1, the preparation process of the precursor dispersion includes: dissolving the binder in an organic solvent to obtain an organic solution, and then adding the inorganic silver salt to the organic solution to obtain the precursor dispersion; Preferably, the amount of the inorganic silver salt added is 20% to 25% based on the total weight of the organic solution being 100%; More preferably, the organic solvent is selected from one or more of N-methylpyrrolidone, acetonitrile and N,N-dimethylformamide.
8. The preparation method according to any one of claims 4 to 7, characterized in that: Both step S1 and step S2 are performed in a dry room environment; Preferably, the temperature of the dry room environment is 20°C to 25°C, and the dew point is -60°C to -40°C.
9. The preparation method according to any one of claims 4 to 8, characterized in that: The heating treatment in step S4 is performed at a temperature of 50°C to 80°C and a time of 0.5h to 2.0h; Preferably, both step S3 and step S4 are performed in an environment where the oxygen content is less than 1 ppm and the water content is less than 1 ppm.
10. An all-solid-state lithium-ion battery, comprising a solid electrolyte layer, characterized in that: The all-solid-state lithium-ion battery is a full battery, and the full battery includes a positive electrode sheet, a negative electrode sheet, and the solid electrolyte layer arranged between the positive electrode sheet and the negative electrode sheet; the positive electrode sheet includes a positive electrode collector and a positive electrode active layer arranged on at least one side surface of the positive electrode collector, and the positive electrode active layer includes a nickel-cobalt-manganese ternary layered oxide; the negative electrode sheet is a silicon-carbon negative electrode sheet according to any one of claims 1 to 3, or a silicon-carbon negative electrode sheet prepared by the method for preparing a silicon-carbon negative electrode sheet according to any one of claims 4 to 9; or, The all-solid-state lithium-ion battery is a half-cell, and the half-cell includes a working electrode, a counter electrode, and the solid electrolyte layer arranged between the working electrode and the counter electrode; the counter electrode is a lithium-indium electrode; the working electrode is the silicon-carbon negative electrode sheet according to any one of claims 1 to 3, or the silicon-carbon negative electrode sheet prepared by the method for preparing the silicon-carbon negative electrode sheet according to any one of claims 4 to 9; More preferably, the solid electrolyte in the solid electrolyte layer is selected from Li7P3S 11 , Li 10 GeP2S 12 , Li6PS5Cl, Li6PS5Br and Li6PS5I, more preferably Li6PS5Cl.
Citation Information
Patent Citations
Lithium anode with inorganic protective coating and preparation method thereof
CN108565398A
Negative pole piece and battery comprising same
CN118367110A
Atomic layer deposition of stable lithium ion conductive interfacial layer for stable cathode cycling
US20200152976A1
Multi-layer lithium metal battery negative electrode, and preparation method and preparation device therefor
US20240186480A1
Cited By
Negative electrode of sulfide solid-state battery, preparation method of negative electrode and sulfide solid-state battery
CN121394301A
A sulfide solid-state battery negative electrode and a preparation method thereof and a sulfide solid-state battery
CN121394301B
Silicon-carbon negative electrode sheet and preparation method therefor, and all-solid-state lithium-ion battery
WO2026091787A1